SPECIFIC FEATURES OF THE SPEECH OF BLIND PRESCHOOL CHILDREN - Maxmudova Madinaxon Sobirxonovna; Qahhorova Maftuna Tolibjonovna (Bright Mind Publishing, 2025)
For human development and growth as a complete person, all its members must function healthily and fully. Unfortunately, not all people are healthy in all respects. Despite this, people with various disabilities also strive for perfection. We can safely include blind people in this group.